Auditor Switching, Financial Distress, and Financial Statement Fraud Practices with Audit Report Lag as Intervening Variable - Fandry Widharma; Endah Susilowati (Journal of Accounting and Strategic Finance, 2020)
This research aims to examine Auditor Switching and Financial Distress's effect on the possibility of Financial Statement Fraud occurrence, which is proxied by using the F-Score formula, and Audit Report Lag Intervening variable. This study's subjects are companies engaged in manufacturing and listed on the Indonesia Stock Exchange (IDX) with a research period in 2014-2018. The sample in this study used a non-probabilistic purposive sampling technique with a total of 27 manufacturing companies. The analysis technique in this study uses Partial Least Square (PLS) with smart PLS 3.0 tools. Results indicate that financial distress and audit report lag directly affect Financial Statement fraud. Auditor report lag as an intervening variable does not influence the relationship between auditor switching, financial distress, and Financial Statement fraud. These results imply that investors must be more careful in investing in the company with a lag in their audit reports. It is also suggested that management must continue to be cautious with the opportunity to do fraud in the financial statement.